Project Planning Practices in State Tourism Corporations - Singh, Manjit (Gyan Management Journal, 2007)
It is on record that a major factor in inadequate performance of enterpri es in lndia ha· been poor quality of investment J cision · in both the private and public sectors of the economy. While identifying new project
Keywords: State Tourism Corporations; quality of investment; economy; political